2020
DOI: 10.1002/nem.2131
|View full text |Cite
|
Sign up to set email alerts
|

Trustful ad hoc cross‐organizational data exchanges based on the Hyperledger Fabric framework

Abstract: Organizations share data in a cross-organizational context when they have the goal to derive additional knowledge by aggregating different data sources. The collaborations considered in this article are short-lived and ad hoc, that is, they should be set up in a few minutes at most (e.g., in emergency scenarios). The data sources are located in different domains and are not publicly accessible. When a collaboration is finished, it is however unclear which exchanges happened. This could lead to possible dispute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Both consider trust issues that arise when different organizations need to collaborate and thus share data. First, a logging mechanism is needed to allow an honest organization to protect itself against potentially malicious partners and to gain trust in the collaboration at hand [5]. Second, it should be possible for an organization to perform checks and balances with respect to container deployments that are suggested for its domain by a potentially malicious external operator [6].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Both consider trust issues that arise when different organizations need to collaborate and thus share data. First, a logging mechanism is needed to allow an honest organization to protect itself against potentially malicious partners and to gain trust in the collaboration at hand [5]. Second, it should be possible for an organization to perform checks and balances with respect to container deployments that are suggested for its domain by a potentially malicious external operator [6].…”
Section: Related Workmentioning
confidence: 99%
“…This boils down to an overview of all nodes and deployed pods, corresponding resource consumption metrics, data flows between the individual organizations based on a logging solution (e.g. like the one proposed by the authors [5]), and alerts by an alerting system. When an application needed for the cross-organizational collaboration shows issues related to quality of service, an operator may decide to reschedule the corresponding pod.…”
Section: Probe Swarm Architecturementioning
confidence: 99%
“…Using this environment, it is possible for an orchestrator to deploy any kind of application in the federated cluster with only minimal installation and configuration input needed from the participating organizations. One such application is proposed in a previous article by the authors, 7 where a logging mechanism using a decentralized database setup is suggested in order to persist logs describing cross‐organizational data exchanges. This mechanism allows an honest organization to protect itself against the potentially malicious behaviour of other participating organizations.…”
Section: Related Workmentioning
confidence: 99%